Biplanar Lateral Hemi-Wedge Osteotomy for the Correction of Severe Tibial Varus Deformity - Wolf Petersen, M.D.; Hassan Al Mustafa, M.D.; Martin Häner, M.D. (Arthroscopy Techniques)
Indication for this hemi-wedge high tibial osteotomy is the combination of medial osteoarthritis or cartilage damage, varus deformity of >10°, and medial proximal tibial angle of <80°. The proximal lateral tibia is exposed via a skin incision of approximately 10 cm length between the tibial tuberosity and the head of the fibula. After detachment of the anterior tibial muscle, a first oblique guidewire marks the main osteotomy plane and a second guidewire marks the hemi-wedge. Then, the osteotomy is performed along the guidewires with an oscillating saw and the laterally based wedge is removed. After percutaneous needling of the medial collateral ligament with a cannula, the lateral gap is closed and stabilized with an angular-stable plate. The rehabilitation protocol includes partial weight-bearing with 10 kg for 6 weeks and free range of motion.